2017
DOI: 10.22489/cinc.2017.207-155
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Range Correlations in Beat Rate Variability of Human Pluripotent-Stem-Cell-Derived Cardiomyocytes

Abstract: A healthy heart exhibits fractal, i.e., long-range correlated fluctuations in heart rate variability (HRV). It is recently shown that fractal dynamics is also an intrinsic feature of human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs). In this study, we investigate short-and long-range correlations in beat rate variability (BRV) of hiPSC-CMs, obtained from a healthy subject and symptomatic and asymptomatic long QT syndrome patients. It is shown that it is important to distinguish correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(14 reference statements)
1
0
0
Order By: Relevance
“…The result indicates that the intrinsic complexity of the hiPSC-CMs can be altered by a diseased state of hiPSC-CMs. It is also in line with our previous study [16], which showed that symptomatic LQT1-CMs exhibit reduced short-term scaling exponents, while healthy and asymptomatic LQT1-CMs have scaling exponents close to 1/f noise throughout the scale.…”
Section: Healthy Vs Diseased Hipsc-cmssupporting
confidence: 93%
“…The result indicates that the intrinsic complexity of the hiPSC-CMs can be altered by a diseased state of hiPSC-CMs. It is also in line with our previous study [16], which showed that symptomatic LQT1-CMs exhibit reduced short-term scaling exponents, while healthy and asymptomatic LQT1-CMs have scaling exponents close to 1/f noise throughout the scale.…”
Section: Healthy Vs Diseased Hipsc-cmssupporting
confidence: 93%